STRATEGI SOCIAL MEDIA MARKETING DAN CONTENT MARKETING TERHADAP BRAND IMAGE PERUSAHAAN (NONNA KITCHEN) - Hasan, Zidny Ilma (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to examine the role of social media marketing and content marketing in shaping brand image in Nonna Kitchen. This study used quantitative methods. Data was collected through a survey with the help of questionnaires and instant messaging media distributed to 120 people who had visited Nonna Kitchen. The data obtained is then processed to test the hypothesis using the help of smartPLS 3.3.0 software. Analysis of quantitative data showed that the two hypotheses tested were significantly supported by the data. This study found important points through the results of the analysis of questionnaire instruments, namely social monitoring strategy and easy to understand content are the main factors in shaping Nonna Kitchen's brand image.